Power to the people : constitutionalism in the age of populism - Tushnet, Mark V., 1945-; Bugariéc, Bojan (New York, NY : Oxford University Press, 2021)
'Power to the People' proposes that some forms of populism are inconsistent with constitutionalism, while others aren't. By providing a series of case studies, some organized by nation, others by topic, the book identifies these populist inconsistencies with constitutionalism - and, importantly, when and how they are not. Opening a dialogue for the possibility of a deeper, populist democracy, the book examines recent challenges to the idea that democracy is a good form of government by exploring possibilities for new institutions that can determine and implement a majority's views without always threatening constitutionalism.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 16, 2021).
Keywords: Constitutional law -- Political aspects; Populism